Cardiovascular protection by combination of the selective nonsteroidal MR antagonist finerenone and the SGLT2 inhibitor empagliflozin in a preclinical model of hypertension-induced end-organ damage. (14th October 2021) - Kolkhof, P; Hartmann, E; Freyberger, A; Pavkovic, M; Mathar, I; Sandner, P; Droebner, K; Joseph, A; Eitner, F; Hueser, J
Abstract: Background: The nonsteroidal mineralocorticoid receptor (MR) antagonist finerenone and SGLT2 inhibitors have demonstrated clinical benefits in HFrEF and CKD patients with T2D. Cardiovascular protection with finerenone and the SGLT2 inhibitor empagliflozin in combination in hypertensive cardiorenal disease is unknown. Purpose: To test the hypothesis that the combination of finerenone with empagliflozin provides cardiovascular protection in preclinical hypertension-induced end-organ damage. Methods: Cardiovascular morbidity and mortality was studied in hypertensive L-NAME (20 mg/L) treated renin-transgenic (mRen2)27 rats. Rats (10–11 weeks old female, n=13–17/group) were treated once daily orally for up to 7 weeks with placebo, finerenone (1 and 3 mg/kg), empagliflozin (3 and 10 mg/kg), or a combination of the respective low doses. Blood pressure (week 1, 3 and 5), urinary (week 2 and 6) and plasma parameters (week 6 and at the end of the study) were determined during the course of the study, while cardiac histology and left ventricular gene expression analysis were performed after study end. Results: Empagliflozin induced a strong and dose-dependent increase in urinary glucose excretion which was not influenced by finerenone co-administration in the combination arm. Treatment with 3 mg/kg finerenone and the low dose combination significantly decreased systolic blood pressure (SBP) after 3 and 5 weeks as well as plasma uric acid after 6 weeks. SBP was significantly more reduced in the combination arm vs. the individual monotherapies after 3 weeks. Plasma NT-proBNP was reduced by empagliflozin, finerenone and the combination with similar efficacy. There was a dose-dependent protection from cardiac vasculopathy, cardiac and vascular fibrosis with both agents while low dose combination therapy was more efficient than the respective monotherapy dosages on these cardiac histology parameters. Placebo-treated rats demonstrated a ca. 50% survival rate over the course of 7 weeks while low dose combination provided the most prominent survival benefit (93%). Conclusion: Non-steroidal MR antagonism by finerenone and SGLT2 inhibition by empagliflozin confer cardiovascular protection in preclinical hypertensive-induced cardiorenal disease. Combination of these two modes of action at low dosages revealed efficacious reduction in blood pressure, cardiac lesions and mortality indicating a strong potential for combined clinical use in cardiorenal patient populations. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): BAYER AG